2006 International Symposium on Ad Hoc and Ubiquitous Computing 2006
DOI: 10.1109/isahuc.2006.4290641
|View full text |Cite
|
Sign up to set email alerts
|

A Routing Protocol for Delay-Sensitive Applications in Mobile Ad Hoc Networks

Abstract: Generally speaking these protocols are classified into two broad categories: proactive (table driven) and on demand The Ad hoc On Demand Distance Vector (AODV) routing routing (source initiated) [4,5,6]. Proactive protocols are less protocol is intended for use by mobile nodes in ad hoc efficient than the later, as they need more network resources networks. To provide quality of service, extensions can be to maintain an up-to-date routing information to every other added to the messages used during route disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…However studies have shown that single path routing based on minimum hop count metrics may not always provide best performance, especially in MANETs when there are nodes along the route which are congested or have less resource such as bandwidth or residual energy [8,9]. In single path routing, the discovered routes may not be reliable because they could easily be broken due to node mobility or unpredictable link conditions, resulting in transmission failures and delay in the network, making the protocol unreliable.…”
Section: Multipath Routing In Manetsmentioning
confidence: 99%
“…However studies have shown that single path routing based on minimum hop count metrics may not always provide best performance, especially in MANETs when there are nodes along the route which are congested or have less resource such as bandwidth or residual energy [8,9]. In single path routing, the discovered routes may not be reliable because they could easily be broken due to node mobility or unpredictable link conditions, resulting in transmission failures and delay in the network, making the protocol unreliable.…”
Section: Multipath Routing In Manetsmentioning
confidence: 99%
“…However, the neighbor suppression mechanism does not check whether it receives the corresponding RREP packet or not. Hence, prevention from unreachable destination [11] is not possible. It is also vulnerable to the RREQ flooding attack conducted by the generation of many different source addresses.…”
Section: Related Workmentioning
confidence: 99%
“…The local density, ζ, of a node is defined as the number of neighboring nodes lying under its transmission range. With respect to local density, Rbuffer(control) and Rbuffer(data) can be defined as in (10) and (11).…”
Section: Proposed Schemementioning
confidence: 99%
See 2 more Smart Citations